Free speech : from core values to current debates / Len Niehoff, E. Thomas Sullivan. - Niehoff, Leonard M.; Sullivan, E. Thomas (Cambridge University Press, 2022)
Why do we protect free speech? What values does it serve? How has the Supreme Court interpreted the First Amendment? What has the Court gotten right and wrong? Why are current debates over free expression often so divisive? How can we do better? In this succinct but comprehensive and scholarly book, authors Len Niehoff and Thomas Sullivan tackle these pressing questions. Free Speech: From Core Values to Current Debates traces the development and evolution of the free speech doctrine in the Supreme Court and explores how the Court - with varying levels of success - has applied that doctrinal framework to "hard cases" and current controversies, such as those involving hate speech, speech on the internet, speech on campus, and campaign finance regulation. This is the perfect volume for anyone - student, general reader, or scholar - looking for an accessible overview of this critical topic.